ASSESSING THE RESPIRATORY CONSEQUENCES OF PAINT FUME INHALATION - Mahalakshmi, J; Kiran Kumar, K; Devasena, B; Swetha, M (The Bioscan, 2025)
Water-based paints are generally considered safer than solvent-based alternatives due to their lower content of volatile organic compounds (VOCs), resulting in reduced toxicity and minimal odor. Natural, VOC-free, and odorless paints, such as eco-friendly options, further minimize health risks by eliminating the release of harmful fumes. Additionally, the use of water for cleaning brushes negates the need for chemical solvents like white spirit or turpentine, which are potential sources of toxic exposure.Despite these advantages, proper precautions remain essential during painting activities. Ensuring adequate ventilation by keeping windows open and allowing fresh air circulation is crucial. Occupants should avoid using freshly painted spaces until the paint has fully dried. Employing protective measures, such as dust sheets and respirator masks, can further reduce exposure to airborne particles.It's important to note that solvents used in paints are highly flammable; therefore, eliminating open flames near paint cans is imperative to prevent fire hazards. Proper disposal of rags and other materials contaminated with oil-based paints is also necessary to avoid spontaneous combustion.Recent studies have highlighted the respiratory health risks associated with exposure to paint fumes. Occupational exposure to VOCs in paints has been linked to increased incidences of cough, dyspnea, nasal/throat irritation, and wheezing among workers. Pulmonary function tests have shown significant reductions in parameters such as forced expiratory volume in one second (FEV1) and FEV1/forced vital capacity (FEV1/FVC) ratios among exposed individuals.